(untitled) (American Journal of Islam and Society, 1994)
Sociology was developed in the western intellectual ethos within a distinct sociopolitical milieu rooted in a postrevolutionary Europe characterized by new tmds of thought that represented serious and sharp teLtctions to the prevailing social situation. Social thinkem of the period expressed an intense desire to develop a new science of Society that, once equipped with adequate methods and theoretical constmcts, could be used to study and better understand society and social phenomena. This new tool would then be used to analyze how the construction and teconstruction of society could be carried out to ameliorate the lot of people. During the sixteenth to eighteenth centuries, European society passed through a tumultuous state and witnessed drastic changes in its Social and intellectual fabrics. The expansion of trade in the sevenknth century led to the crumbling of the economic order and the emergence of its new mastem: guilds and charted corporations. The eighteenth century replaced this system with that of free labor and competitive production. The emergence of large-scale industries structured the economic organization anew and accelerated both pduction and profit. Competition fotced industries to develop new technology in order to increase production and produce better quality goods. Markets were explod and expanded, and trade was encouraged. This economic mrganization affected the pattern of social life, as the ensuing population shift from the rural to urban areas altered the extant family structure. In addition, the rule of law began to be considered necessary for the smooth functioning of the new economic order. These developments gradually transformed the feudal order and the transitory mercantile order into a capitalist economic system that created ...